The impact of governance and good governance on the structure of local administration summary - Podgórniak-Krzykacz, Aldona (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Article describes the issues of shaping the structures of local government administration considering new concepts of public management. Attention will be focused on governance, which determines two paradigms of public administration: public administration aimed at cooperation and organized in a network manner. Will evaluate the degree of their impact on the structure of local government administration in Poland. Further considerations will aim to identify the relationship between the quality of governance and administrative structure of local government. The quality of governance is recognized (by the World Bank) in six dimensions of good governance, which is a function of appropriately shaped bodies. Striving to meet the criteria of good governance may involve restrictions on the use of cooperation and networking paradigms.